Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What is known about solutions in integers of the equations; $x^4 - y^2 = z^6$

I got $x=4st(s^4 - t^4)$ , $z=4st(s^2 - t^2)$ , $y=(4st(s^2 - t^2))^2 (s^4 + t^4 - 6 (st)^2) $

and, the equation $x^2 - y^4 = z^6 $

I got $y=4st(s^4 - t^4) , z=4st(s^2 + t^2) , x=(4st(s^2 + t^2))^2 (s^4 + t^4 + 6 (st)^2)$

share|improve this question
    
How did you get these solutions? –  Berci Oct 5 '12 at 10:36
    
@Berci:As I said in another post,I got x=4mn(m+n) , y=4mn(m-n) , z=4mn for x^2 - y^2 = z^3. Then once I put m = (s^2 - t^2)^2 and n=4(st)^2 and got the solution for x^4 - y^2 = z^6 ; and after thinking over some time I put m=(s^2 + t^2)^2 and n=4(st)^2 and got the solution of x^2 - y^4 = z^6 –  Souvik Dey Oct 5 '12 at 10:49

1 Answer 1

up vote 1 down vote accepted

Here is another solution of $x^4 - y^2 = z^6$. Suppose we have a Pythagorean triple $a^2 + b^2 = c^2$, and c is itself a square, say $d^2$. There are many such solutions, a sufficient condition being that c can be factorised into primes of the form $4n+1$, with an even exponent of each prime. Where this is the case each factor can be expressed as a sum of two squares (Fermat's 4n+1 Theorem), then we can use Brahmagupta's identity to express c as a sum of two squares, say $m^2 + n^2$. Then using the standard formula for Pythagorean triples we put a and b equal to $m^2 - n^2$ and $2mn$ (in either order).

Given $a^2 + b^2 = d^4$ we have:

$d^4 - a^2 = b^2$

$(d^4)(b^4) - (a^2)(b^4) = (b^2)(b^4)$

$(bd)^4 - (ab^2)^2 = b^6$

The smallest non-trivial solution of this type has a = 24, b = 7, c = 25, d = 5, yielding $35^4 - 1176^2 = 7^6$. Each such Pythagorean triple yields two solutions by reversing a and b, the second solution in this case with a = 7, b = 24 being $120^4 - 4032^2 = 24^6$. The second solution is an instance of the solution in the question (with s = 2, t = 1), but the first is not (since 4 does not divide 35 or 7). More generally, any solution of the above form with b and d both odd will result in x odd and therefore not be an instance of the solution in the question.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.